Ecological and Economic Aspects of Bio-diversity Conservation in a Protected Area, India - Ninan, K.N.; Sathyapalan, Jyothis (Macmillan India, 2005)
This paper analyses the economics of biodiversity conservation in the context of a tropical forest ecosystem in the Western Ghats region of India, where coffee is the main competitor for land use. Using primary data covering a cross-section of coffee growers, the study notes that the opportunity costs of biodiversity conservation in terms of coffee benefits foregone are quite high. Even after including external costs due to wildlife damages and defensive expenditure to protect against wildlife, the NPVs and IRRs from coffee for all land holding groups were high. Including external costs, these NPVs across different land holding groups ranged between Rs 17 thousand to over Rs 106 thousand per acre at 12% discount rate, and the IRRs between 16.6% and 23%. Even if the expected benefits were to decrease by 20% and costs rise by a similar proportion, still the IRRs from coffee were quite high (19.5-20.1%). The study notes that the external costs accounted for between 7% and 15% of the total discounted costs of coffee cultivation, and smaller holdings proportionately incurred higher external costs as compared to large holdings. The study also notes high transaction costs incurred by the growers to claim compensation for wildlife damages. Notwithstanding these disincentives, the study notes that the local community had a positive attitude towards biodiversity conservation and were willing to pay in terms of spending time for participatory biodiversity conservation. Taking elephants, a keystone and threatened species in Asia and the study region, for the contingent valuation survey, the study notes that the respondents are willing to spend 25.8 humandays per household annually which works to over Rs 6003 per household per annum in terms of the income foregone. They also preferred a decentralized government institution for participatory biodiversity conservation.
Keywords: Bio-diversity Conservation; Ecology; Economics; Quality of Life